Modelling the mesoscale variability in the greater Agulhas Current system using hybrid coordinate Ocean model - Backeberg, Bjorn Christoph (Department of Oceanography, 2014)
The ocean circulation dynamics in the greater Agulhas Current system are dominated by mesoscale variability, which is highly non-linear, and therefore difficult to measure and simulate accurately. Moreover, the shedding of Agulhas rings from the retroflection south of Africa, which is the dominant mechanism by which warm and saline water flows from the Indian into the Atlantic Ocean, is thought to be a crucial component of the thermohaline circulation. With the goal of providing an accurate simulation of the greater Agulhas Current system, and in particular its mesoscale variability, a high resolution Hybrid Coordinate Ocean Model is set up in a nested configuration. In two 11 year simulation experiments, the effect of a higher order momentum advection scheme on the simulated ocean dynamics is tested and evaluated against available satellite observations and in-situ measurements. Quantitative analyses and model validation methods are developed to objectively evaluate the simulation experiments. The resultant skewness analyses and spatial variograms are objective measures for assessing the model simulation and additionally provide new insights on the mesoscale dynamics of the greater Agulhas Current system. A 4th order momentum advection scheme is shown to significantly improve the simulation of the region, in particular the dynamics of the southern Agulhas Current and the retroflection are greatly improved. From the analyses of the two model simulations in conjunction with satellite observations and in-situ measurements, it is found that the Indo-Atlantic inter-ocean exchange, and the shedding of Agulhas rings from the retroflection, is sensitive to the strength of the Agulhas Current, which in turn is influenced by the flow dynamics in the Mozambique Channel and south of Madagascar. Mesoscale eddies drifting from these source regions to the Agulhas Current play an important role, and the connection between the Agulhas Current and the respective source regions provides a link to large-scale variability in the Indian Ocean, which in turn is related to interannual modes of variability such as the Indian Ocean Dipole and El NiÑo Southern Oscillation.